The Jewish-Christian encounter in medieval preaching
1 online resource (x, 334 pages)
Keywords: "This book explores the complexity of preaching as a phenomenon in the medieval Jewish-Christian encounter. This was not only an "encounter" as physical meeting or confrontation (such as the forced attendance of Jews at Christian sermons that took place across Europe), but also an "imaginary" or theological encounter in which Jews remained a figure from a distant constructed time and place who served only to underline and verify Christian teachings. Contributors also explore the Jew.sh response to Christian anti-Jewish preaching in their own preaching and religious instruction"--